2021
DOI: 10.5312/wjo.v12.i6.433
|View full text |Cite
|
Sign up to set email alerts
|

Arthroereisis in juvenile flexible flatfoot: Which device should we implant? A systematic review of literature published in the last 5 years

Abstract: BACKGROUND Flexible flatfoot (FFF) is a very common condition in children, characterized by the loss of the medial arch and by an increase in the support base with valgus of the hindfoot. Arthroereisis (AR) procedures are widely performed corrective surgeries and are classified as subtalar AR and calcaneo-stop (CS). AIM We investigated the literature published in the last 5 years with the aim of providing an update on the evidence related to AR treatment in FFF patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…Our findings are similar to those of previous studies, indicating that arthroeresis yields improved gait pattern and less pain [ 13 15 ]. Indino et al found that subtalar arthroereisis with endorthesis was effective for treating paediatric flexible flatfoot, reflected in improved radiographic parameters at skeletal maturity [ 20 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are similar to those of previous studies, indicating that arthroeresis yields improved gait pattern and less pain [ 13 15 ]. Indino et al found that subtalar arthroereisis with endorthesis was effective for treating paediatric flexible flatfoot, reflected in improved radiographic parameters at skeletal maturity [ 20 ].…”
Section: Discussionsupporting
confidence: 92%
“…They found no significant differences in radiographic or clinical parameters between the two groups in the short and medium term. A recent systematic review ( 41 ) showed that both impact blocking and self-locking devices were proven to be valid and effective for treating pediatric flexible flatfeet. Nonetheless, for those with obesity or those demanding high performance in sports, the calcaneo-stop procedure may be better and more recommended ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review ( 41 ) showed that both impact blocking and self-locking devices were proven to be valid and effective for treating pediatric flexible flatfeet. Nonetheless, for those with obesity or those demanding high performance in sports, the calcaneo-stop procedure may be better and more recommended ( 41 ). The calcaneo-stop procedure, a cheap, simple, and effective technique, has shown satisfactory clinical and radiographic outcomes and low rates of complications ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…At this point, for the clinical practitioner, in the decision-making process, it is essential to distinguish between the different forms of flatfoot-asymptomatic or symptomatic flexible flatfoot. If the child expresses pain in the feet, and the parents also have concerns about the shape of the child's feet, this commonly used combination opens up the possibility of using an understandable and approved treatment algorithm for flexible symptomatic flatfoot [1,4,[18][19][20][21][22][23]. On the other hand, if the child does not express or note pain in the feet, but only the parents are worried about the child's flat feet, then clinicians should alleviate their parents' worry and explain that children are born with flexible flatfoot which naturally develops the normal arch in the first decade of life or remains asymptomatic [24].…”
Section: Introductionmentioning
confidence: 99%